Arterial Blood Supply to the Spinal Cord in Animal Models of Spinal Cord Injury. A Review. Issue 12 (13th October 2017) - Mazensky, David; Flesarova, Slavka; Sulla, Igor
ABSTRACT: Animal models are used to examine the results of experimental spinal cord injury. Alterations in spinal cord blood supply caused by complex spinal cord injuries contribute significantly to the diversity and severity of the spinal cord damage, particularly ischemic changes. However, the literature has not completely clarified our knowledge of anatomy of the complex three‐dimensional arterial system of the spinal cord in experimental animals, which can impede the translation of experimental results to human clinical applications. As the literary sources dealing with the spinal cord arterial blood supply in experimental animals are limited and scattered, the authors performed a review of the anatomy of the arterial blood supply to the spinal cord in several experimental animals, including pigs, dogs, cats, rabbits, guinea pigs, rats, and mice and created a coherent format discussing the interspecies differences. This provides researchers with a valuable tool for the selection of the most suitable animal model for their experiments in the study of spinal cord ischemia and provides clinicians with a basis for the appropriate translation of research work to their clinical applications. Anat Rec, 300:2091–2106, 2017. © 2017 Wiley Periodicals, Inc.